2021
DOI: 10.3390/foods10071541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulsed Electric Fields (PEF) on Extraction Yield and Stability of Oil Obtained from Dry Pecan Nuts (Carya illinoinensis (Wangenh. K. Koch))

Abstract: Pulsed electric fields (PEF) have been reported to increase the total oil extraction yield (OEYTOTAL) of fresh pecan nuts maintaining oil characteristics and increasing phenolic compounds in the remaining by-product. However, there is no information regarding the PEF effect on dry pecan nuts. Dry kernels were pretreated at three specific energy inputs (0.8, 7.8 and 15.0 kJ/kg) and compared against untreated kernels and kernels soaked at 3, 20 and 35 min. OEYTOTAL, kernels microstructure, oil stability (acidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…6 A-D). This result shows a certain similarity with the previous result where it was shown that PEF treatment enhanced the antioxidant capacity of walnut oil and improved DPPH ( Rábago-Panduro, Romero-Fabregat, Martín-Belloso, & Welti-Chanes, 2021 ).
Fig.
…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…6 A-D). This result shows a certain similarity with the previous result where it was shown that PEF treatment enhanced the antioxidant capacity of walnut oil and improved DPPH ( Rábago-Panduro, Romero-Fabregat, Martín-Belloso, & Welti-Chanes, 2021 ).
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, as reported by Ćurko et al (2023) , the application of PEF treatment increased the total phenolic content as well as the oxygen radical absorbance capacity (ORAC) of grape seed oil. In addition, Rábago-Panduro, Romero-Fabregat, Martín-Belloso and Welti-Chanes (2021) found that PEF significantly improved the ability of walnut oil to scavenge free radicals such as DPPH and increased oil yield. Few studies have investigated the possible effects of PEF on the total flavonoid, polyphenol, and pigment content, as well as the in vitro antioxidant capacity of VOO, despite the fact that prior research has shown the positive effects of PEF on the oil yield, acidity, and phenolic compounds amount in VOO.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, testa is present is the barrier between cotyledon and environment. Such an arrangement of cells make pecan testa more susceptible to moisture absorption (Rábago‐Panduro, Morales‐de la Peña, Romero‐Fabregat, Martín‐Belloso, & Welti‐Chanes, 2021 ). As moisture in the pecan increases, the compact cells start to swell and have greater cell wall flexibility and an increase in the intracellular distance, causing loss of fracturability.…”
Section: Discussionmentioning
confidence: 99%
“… Light microscopy micrographs of the testa (Ts) and cotyledon tissue (Ct) of dry pecan nuts, adapted from Rábago‐Panduro, Morales‐de la Peña, Romero‐Fabregat, Martín‐Belloso, and Welti‐Chanes ( 2021 ) …”
Section: Discussionmentioning
confidence: 99%
“…Rábago-Panduro et al [ 13 ] investigated the effect of pulsed electric fields on the extraction yield and stability of oils obtained from pecan nuts ( Carya illinoinensis (Wangenh. K. Koch)).…”
mentioning
confidence: 99%